Measurement of activity of urea resistant neutrophil alkaline phosphatase as an antenatal screening test for Down's syndrome. Issue 6759 (3rd November 1990) - Cuckle, H S; Wald, N J; Goodburn, S F; Sneddon, J; Amess, J A; Dunn, S C
Abstract : OBJECTIVE--To investigate the value of measuring maternal urea resistant neutrophil alkaline phosphatase activity as an antenatal screening test for Down's syndrome. DESIGN--Case-control study of blood samples collected at nine to 27 weeks of pregnancy. SETTING--Antenatal clinics in London and Oxford. PATIENTS--72 Women whose fetuses had been diagnosed by amniocentesis or chorionic villus sampling as having Down's syndrome and 156 women whose fetuses did not have the syndrome. Only singleton pregnancies were studied. MAIN OUTCOME MEASURE--Activity of urea resistant neutrophil alkaline phosphatase measured cytochemically. RESULTS--The median enzyme activity in the index patients was 1.65 times the expected median for the controls at the same duration of pregnancy (p less than 0.0001; 95% confidence interval 1.56 to 1.74). A cut off value that identified the 5% of control patients with the highest activities yielded a rate of detection of Down's syndrome of 79% (95% confidence interval 70 to 89%). CONCLUSION--Activity of urea resistant neutrophil alkaline phosphatase is an effective maternal blood marker for Down's syndrome. Its use in antenatal screening could lead to a substantial improvement in the detection of this disorder. Before introducing the test into routine medical practice it will have to be automated so that it can be used on a large scale and is less subjective.